Nocardia Infection in Solid Organ Transplant Recipients: A Multicenter European Case-control Study. (18th April 2016) - Coussement, Julien; Lebeaux, David; van Delden, Christian; Guillot, Hélène; Freund, Romain; Marbus, Sierk; Melica, Giovanna; Van Wijngaerden, Eric; Douvry, Benoit; Van Laecke, Steven; Vuotto, Fanny; Tricot, Leïla; et al.
Abstract : In this European multicenter case-control study, Nocardia infection after organ transplant was associated with high blood concentrations of calcineurin inhibitors, use of tacrolimus, dose of corticosteroids, patient age, and length of stay in the intensive care unit after transplant. Abstract : Background.  Nocardiosis is a rare, life-threatening opportunistic infection, affecting 0.04% to 3.5% of patients after solid organ transplant (SOT). The aim of this study was to identify risk factors for Nocardia infection after SOT and to describe the presentation of nocardiosis in these patients. Methods.  We performed a retrospective case-control study of adult patients diagnosed with nocardiosis after SOT between 2000 and 2014 in 36 European (France, Belgium, Switzerland, the Netherlands, Spain) centers. Two control subjects per case were matched by institution, transplant date, and transplanted organ. A multivariable analysis was performed using conditional logistic regression to identify risk factors for nocardiosis. Results.  One hundred and seventeen cases of nocardiosis and 234 control patients were included. Nocardiosis occurred at a median of 17.5 (range, 2–244) months after transplant. In multivariable analysis, high calcineurin inhibitor trough levels in the month before diagnosis (odds ratio [OR], 6.11; 95% confidence interval [CI], 2.58–14.51), use of tacrolimus (OR, 2.65; 95% CI, 1.17–6.00) and corticosteroid dose (OR, 1.12; 95% CI, 1.03–1.22) at the time of diagnosis, patient age (OR, 1.04; 95% CI, 1.02–1.07), and length of stay in the intensive care unit after SOT (OR, 1.04; 95% CI, 1.00–1.09) were independently associated with development of nocardiosis; low-dose cotrimoxazole prophylaxis was not found to prevent nocardiosis. Nocardia farcinica was more frequently associated with brain, skin, and subcutaneous tissue infections than were other Nocardia species. Among the 30 cases with central nervous system nocardiosis, 13 (43.3%) had no neurological symptoms. Conclusions.  We identified 5 risk factors for nocardiosis after SOT. Low-dose cotrimoxazole was not found to prevent Nocardia infection. These findings may help improve management of transplant recipients.